KEPEMIMPINAN PENDIDIKAN ISLAM DALAM PERSPEKTIF INTERDISIPLINER - Jayadi, Usman (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2020)
Technological progress will have an impact on social changes in society. Along with these advances, the challenges of leadership has also changed in the face of these technological changes. This study tried to examine various literatures related to leadership, politics and technological challenges in an effort to find the problems of the study to be discussed. Then the findings were as follows; First, leadership from a sociological perspective is leadership that faces challenges in accordance with technological developments. To deal with it, then as a leader it is necessary to implement the AGIL system by holding principles in Islam. Second, leadership from a political perspective is a leader who has challenges with individuals, institutions, organizations, parties and other institutions so that in facing these challenges, all leaders need to prepare themselves to face the challenges of these requirements and compete in a healthy manner without expecting outside help or political money.